2019
DOI: 10.1136/bmjopen-2019-030341
|View full text |Cite
|
Sign up to set email alerts
|

Exploring reasons for differences in performance between UK and international medical graduates in the Membership of the Royal College of General Practitioners Applied Knowledge Test: a cognitive interview study

Abstract: ObjectivesInternational medical graduates (IMGs) perform less well in national postgraduate licensing examinations compared with UK graduates, even in computer-marked multiple-choice licensing examinations. We aimed to investigate thought processes of candidates answering multiple- choice questions, considering possible reasons for differential attainment between IMGs and UK graduates.DesignWe employed a semistructured qualitative design using cognitive interviews. Systematic grounded theory was used to analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 34 publications
2
19
0
Order By: Relevance
“…However, these students are eligible for the FP and specialty training pathways in the same way as ‘home’ students, and their continued contribution to the medical workforce and healthcare delivery is expected and indeed required. Unlike international medical graduates who come to the UK to work after graduating in another country,57–62 international students who graduate from UK medical students are a relatively understudied group. The relative patterns of this group compared with ‘home’ students merit further research.…”
Section: Discussionmentioning
confidence: 99%
“…However, these students are eligible for the FP and specialty training pathways in the same way as ‘home’ students, and their continued contribution to the medical workforce and healthcare delivery is expected and indeed required. Unlike international medical graduates who come to the UK to work after graduating in another country,57–62 international students who graduate from UK medical students are a relatively understudied group. The relative patterns of this group compared with ‘home’ students merit further research.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, this is the same licensing exam used for peers educated within the country. [1][2][3][4][5] However, the pass rate of MPs is usually lower. This delays their licensing, which has negative effects on both MPs and on the new country in need of physicians.…”
Section: Introductionmentioning
confidence: 99%
“…Studies from Australia, Canada, the UK, the USA and Sweden have shown a considerably lower success rate on exams for MPs than for nationally trained physicians. [1][2][3][4][5][6] These exams include those mandated before receiving a medical licence and those required for specialist/postgraduate training. 1-3 7 8 In Sweden, over 30% of MPs with a medical degree from outside the European Union/European Economic Area (EU/EEA) fail to pass the licensing examination on the first attempt, while the corresponding figure for nationally trained physicians is approximately 3%.…”
Section: Introductionmentioning
confidence: 99%
“…The concept for this course resulted from informal 'interview practice' sessions with many non-UK graduates and non-rst-time applicants. There is a perception amongst these groups that they are disadvantaged by individual factors (6). Non-UK graduates struggle to communicate their knowledge effectively in a time-limited, pressurised environment (7).…”
Section: Discussionmentioning
confidence: 99%